The role of ultrasound in screening newborns for developmental! dysplasia op the hip in Hospital Universiti Sains Malaysia, Kelantan - Ali, Rofiah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2005)
This study is to determine the normal values of the alpha and beta angles in normal newborns and to describe the changes of the angles during stress maneuver by ultrasound. Coronal examinations of the hip at rest and stress were performed using a high frequency linear ultrasound probe (5-7.5 MHz) on 49 newborns at Hospital Universiti Sains Malaysia from January 2003 till March 2004. The means of the alpha angles of the right and left hips without stress were 62.0 degrees (SD ± 6.4 degrees), 62.0 degrees (SD ± 5.6 degrees) respectively and with stress were 63.3 degrees (SD ± 7.2 degrees), 59.8 degrees (SD ± 8.0 degrees). The means of the beta angles of the right and left hips without stress were 56.8 degrees (SD ± 7.4 degrees), 56.2 degrees (SD ± 7.0 degrees) respectively and with stress were 54.9 degrees (SD ± 7.1 degrees), 58.2 degrees (SD ± 8.7 degrees). The normal alpha and beta angles of the hip joints were comparable with the Caucasians. There was significant difference in the alpha and beta angle without and with stress.